Artefactual ST segment abnormalities due to electrocardiograph design. Issue 2 (August 1985) - Tayler, D I; Vincent, R
Abstract : Specifications recommended for electrocardiographs omit any reference to phase characteristics and place undue emphasis on an extended amplitude response. This does not, however, ensure faithful reproduction of the electrocardiogram and may result in less effective attenuation of unwanted noise than can be achieved with modern filters. The separate effects of phase and amplitude response on electrocardiographic signals were compared, and it was shown that distortion of the electrocardiogram by equipment with an inadequate phase response may cause changes resembling those seen in ischaemic heart disease. Case reports are presented in which distortion produced by commercial equipment impeded diagnosis. Specifications recommended as standard for electrocardiographs should be modified to include phase response and allow greater attenuation of frequencies below 0.5 Hz.